Improper Diving Behavior Affects Physiological Responses of Acropora hyacinthus and Porites cylindrica - Zhang, Yu; Huang, Jianzhong; Li, Xinke; Song, Cuiping; Xia, Jingquan; Ren, Yuxiao; Wang, Aimin; Li, Xiubao (Frontiers in Marine Science, 2021)
Human activities beyond ecosystem capacity have resulted in serious effects on corals worldwide. Nowadays, many studies have focused on the influence of diving activities on coral communities, while the knowledge of physiological changes under corresponding environmental stresses remains largely undetermined. In the study, we aimed to investigate the physiological effects of touching, ammonia nitrogen enrichment (5 μmol⋅L–1), and sediment cover (particle size of less than 0.3 mm), which simulated improper self-contained underwater breathing apparatus (SCUBA) diving behaviors, on Acropora hyacinthus and Porites cylindrica in Wuzhizhou Island, the South China Sea. For A. hyacinthus, continuous touching caused the tentacles to shrink and secrete mucus, which consumed energy and dissolved oxygen. The skeletal growth rate was decreased by 72% compared with the control group. There was a rapid decline of Fv/Fm and alpha under the dual impacts of high ammonia nitrogen and touching, while the Chl a concentration and tissue biomass were decreased by 36 and 28% compared with touching alone, respectively. High ammonia nitrogen and touching increased the concentrations of lipid and protein. Nevertheless, zooxanthellae density was increased by 23% to relieve the effects of a lower concentration of Chl a in a high nutrient environment. Constant touching and sediment cover in diving areas with elevated ammonia content affected the photosynthesis and respiration of corals, and a significant decrease was observed for lipid, zooxanthellae density, and Chl a concentration. Coral bleaching occurred on day 7. For P. cylindrica, the decreasing magnitude of Fv/Fm and alpha under different stresses in the subsequent phase was less compared with A. hyacinthus. The contents of carbohydrate and protein under continuous touching were decreased by 7 and 15% compared with the control group, respectively, causing negative growth. Under the dual influences of high ammonia nitrogen and continuous touching, all energy reserves were significantly lower. Repeated touching and sediment cover in diving areas containing high ammonia content increased the concentrations of lipid and protein compared with the touching and high nutrient treatment group likely because that Porites associated with C15 zooxanthella increased heterotrophic feeding to compensate for restricted symbiodiniaceae photosynthesis. Additionally, P. cylindrica produced mucus to aid the removal of sediment, so that corals didn’t obviously bleach during the experiment. Collectively, P. cylindrica was more resistant to diving activities than A. hyacinthus which only relies on photoautotrophy. To ensure the sustainable development of coral reef dive tourism, it is necessary to strengthen the supervision of diving behaviors, rotate the diving areas, and conduct regular assessments on the coral status.